APLIKASI PERSAMAAN GELOMBANG UNTUK MENENTUKAN KARAKTERISTIK GELOMBANG SENAR GITAR YANG DIPETIK - Yuni Yulida; Haidir Ahsana; Muhammad Mahfuzh Shiddiq; Muhammad Ahsar Karim (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2021)
Partial differential equations are often used to explain physical phenomena, one of which is the wave equation. One application of the wave equation is in plucked strings. This study describes the formation of a wave equation from guitar strings, determines the solution to the wave equation by using the variable separation method and certain boundary conditions and initial conditions, determines the amplitude of the wave, and simulates the movement of the wave based on the initial position of the plucked string. The result obtained is the wave equation of the guitar strings. When the string is plucked, the string will vibrate and produce a wave that can be formulated as a wave equation in the form of a homogeneous second order partial differential equation. The solution to this equation is in the form of a series. If given the initial conditions of plucking in the form of a function, then the amplitude of the wave is obtained. Simulations are given to see the movement of the amplitude and wave on the strings through three cases of the initial position of plucking the strings, namely: less than half, half, and more than half the length of the strings. The behavior of these amplitudes and waves is a characteristic or characteristic of the waves produced from a plucked guitar string